Agreement between cranial and facial classification through clinical observation and anthropometric measurement among envigado school children (2014)
Background: To evaluate the agreement between cranial and facial classification obtained by clinical observation and anthropometric measurements among school children from the municipality of Envigado, Colombia.Methods: This cross-sectional study was carried out among 8-15-year-old children. Initially, an indirect clinical observation was made to determine the skull pattern (dolichocephalic, mesocephalic or brachycephalic), based on visual equivalence of right eurion- left eurion and glabella-opisthocranion anthropometric points, as well as the facial type (leptoprosopic, mesoprosopic and euryprosopic), according to the left and right zygomatic, nasion and gnation points. Following, a direct measurement was conducted with an anthropometer using the same landmarks for cranial width and length, as well as for facial width and height. Subsequently, both the facial index [euryprosopic (=80.9%), mesoprosopic (between 81% - 93%) and leptoprosopic (=93.1%)] and the cranial index [dolichocephalic (index = 75.9%), mesocephalic (between 76% - 81%), and brachycephalic (=81.1%)] were determined. Concordance between the indices obtained was calculated by direct and indirect measurement using the Kappa statistic.Results: A total of 313 students were enrolled; 172 (55%) were female and 141 (45%) male. The agreement between the direct and indirect facial index measurements was 0.189 (95% CI 0.117-0261), and the cranial index was 0.388 (95% CI 0.304-0.473), indicating poor concordance.Conclusions: No agreement was observed between direct measurements conducted with an anthropometer and indirect measurements via visual evaluation. Therefore, the indirect visual classification method is not appropriate to calculate the cranial and facial indices. © 2014 Torres-Restrepo et al.; licensee BioMed Central Ltd.